Non-electronic visual system for flexible manipulators - Maciel, Ana Luiza Cantharino; Ramalho, Jéssica Guerreiro Santos; Silva, Lucas Cruz Da; Gonçalves, Maria Eduarda Benfica; Silva, Valéria Loureiro Da (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2023)
Flexible robots are a novel technology particularly attractive for inspection in hard-to-reach areas. For operation in environments with potentially explosive atmospheres, care must be taken to eliminate the risk of sparks and ignition sources without burdening the robot with an increase in size and weight. In this paper, a visual system for a flexible and continuous robot manipulator that uses a coherent fiber optic imaging guide is proposed and demonstrated. The use of the image guide allows remote capturing of the image, making the manipulator intrinsically safe for an explosive atmosphere environment. Imaging results displayed the necessary level of detail for inspection of offshore installations.